Favorable breast cancer mortality-to-incidence ratios of countries with good human development index rankings and high health expenditures - Chia-Yu Chou; Tzu-Tsen Shen; Wen-Ching Wang; Ming-Ping Wu (Taiwanese Journal of Obstetrics & Gynecology, 2024)
Objective: Breast cancer is the most frequently diagnosed cancer among women worldwide. Mortality-to-incidence ratio (MIR) is a marker that reflects the efficacy and availability of screening interventions and treatment outcomes. MIR can be used to influence public health strategy. The association between the MIRs for breast cancer among countries with different economic statuses and health expenditure is important yet has been investigated. This study was aimed to elucidate the association between the breast cancer MIRs and the human development and health expenditure among different countries. Materials and methods: Cancer incidence and mortality rates were obtained from the GLOBOCAN database. The MIRs were calculated by dividing the crude rate of mortality to the incidence. Associations among the MIR and variants of human development index (HDI) and current health expenditure (CHE) in 50 countries were estimated via linear regression. Results: Breast cancer had a higher incidence rate, but lower mortality rate, in developed countries (high HDI, CHE per capita, CHE/GDP), as compared with developing countries. Favorable MIRs were associated with a high HDI and high health expenditure countries (presented by high CHE per capita, and CHE/GDP) (both p < 0.001) Conclusion: The MIR for breast cancer is reversely correlated with the development and healthcare disparities among different countries. This implies that allocating more resources to healthcare systems for breast cancer screening and treatment can improve disease outcomes. Our report may be helpful for public health policy making.